Peran Vitamin D dalam Penanganan Pasien Covid-19 - Dwi Widi Mandasari; Maya Tejasari; Widayanti (Bandung Conference Series: Medical Science, 2022)
Abstract. Corona Virus Disease-2019 (Covid-19) is a serious global problem that still needs to be addressed at this time. Covid-19 is caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). One of the Covid-19 prevention measures related to nutrition is the consumption of vitamin D. This study is a Scoping review, a systematic search was carried out through 3 databases (PubMed, Spinger Link, Science Direct,) that met the eligibility criteria. The search results from a total of 5,662 articles contained 494 according to the inclusion criteria, namely 2019 - 2021, observational, experimental, full text, in English and obtained 8 articles according to PICOS. The results of a review and analysis of 9 articles, all of which showed that there was a reduced risk of mortality in the group given vitamin D supplements than the control group that was not given vitamin D. Vitamin D inactivates viral pathogens or inhibits viral replication. So it has a positive effect on the immune system. And useful for handling Covid-19 patients. The conclusion of this study is that the administration of vitamin D can reduce the risk of mortality and increase improvement in the treatment of COVID-19 patients. Abstrak. Corona Virus Disease-2019 (Covid-19) menjadi masalah global serius yang masih perlu ditanggulangi saat ini. Covid-19 disebabkan oleh virus Severe Acute Respiratory Syndrom Coronavirus-2 (SARS-CoV-2). Salah satu langkah pencegahan Covid-19 yang terkait bidang gizi adalah konsumsi vitamin D. Penelitian ini merupakan Scoping review, pencarian sistematis dilakukan melalui 3 database (PubMed, Spinger Link, Science Direct,) yang memenuhi kriteria kelayakan. Hasil pencarian dari total 5.662 artikel terdapat 494 sesuai dengan kriteria inklusi yaitu 2019 - 2021, observasioal, eksperimental, full text, berbahasa Inggrisdan didapatkan 8 artikel sesuai PICOS. Hasil telaah dan analisis dari 9 artikel, semua artikel menunjukan bahwa terjadi penurunan resiko mortalitas pada kelompok yang diberi suplemen vitamin D daripada kelompok kontrol yang tidak diberikan vitamin D. Vitamin D menonaktifkan patogen virus atau menghambat replikasi virus. sehingga memiliki efek positif untuk system kekebalan tubuh. Dan bermanfaat untuk penanganan pasien covid-19. Simpulan dari penelitian ini adalah pemberian vitamin D dapat mengurangi resiko mortalitas serta meningkatkan perbaikan dalam penanganan pasien covid-19.